Living Kidney Transplant: The Influence of Intra-Operative Hemodynamics on Delayed Graft Function - Ryan J. Schutt; Jamie Case; Bethany Barrick; Alice E. Toll; Randolph L. Schaffer; Jonathan S. Fisher; James C. Rice; Christopher L. Marsh (Journal of Organ Transplantation, 2017)
Purpose Intra-operative insults may subject living kidney transplants to poor outcomes. Therefore, we investigated whether intra-operative recipient and donor hemodynamics could act as predictors of delayed graft function and subsequent outcomes. Materials and Methods Living kidney donors and recipients from 2010-2016 at this institution underwent a retrospective chart review. Graft function by post-operative day 7 was used to classify recipients as delayed graft function (need for dialysis), slow graft function (creatinine > 2.5) and good function. Groups were analyzed for intra-operative hemodynamic differences and at one year, incidence of rejection, graft function and survival were compared. Results A total of 111 living renal transplants were performed. Average recipient age was 50 and just over halfwere male (53%). 9% (n=10) and 10% (n=11) developed delayed graft function and slow graft function, respectively. Minimum recipient post re-perfusion central venous pressure ≥12 mmHg was associated with poor graft function (delayed graft function/slow graft function/good function=67%/56%/24%, p=0.009), while intra-operative hypotension (systolic <90 mmHg or diastolic <50 mmHg) was not. Delayed graft function and slow graft function had higher incidences of rejection than good function (30% and 36% vs 9%, p=0.012). Graft function and survival were similar. One patient died with a functioning graft. Conclusions This single center retrospective study suggests that a post re-perfusion central venous pressure ≥12 mmHg is associated with delayed graft function.
Keywords: living kidney transplant